KOMPETENSI PEMODELAN MATEMATIKA SISWA KELAS XI DITINJAU DARI TINGKAT KEMAMPUAN MATEMATIS - Prisilia, Agnes Arum; Hayuhantika, Diesty (Universitas Batanghari Jambi, 2025)
Mathematical modeling competence is crucial for helping students connect mathematical concepts to real-word problems. However, many students struggle to construct mathematical models accurately. This study aims to describe the mathematical modeling competence of eleventh-grade students at a high school in Tulungagung based on their mathematical was employed, involving six students categorized into high, and low mathematical abilities. The instrument used icluded word problem test and interviews. The result indicate that high-ability students can fulfill all mathematical modeling sub-competencies, and low-ability students fail to meet most.